A angústia e a ansiedade na psicopatologia fundamental - Simonetti, Alfredo (2011)
This is a research on the distinction between anguish and anxiety in Fundamental Psychopathology. Starting from the clinical narrative of two patients in attendance in a private clinic, which framed the scenario, a review was carried out on the literature, as a preliminary step, regarding the history of psychopathology, so that relevant aspects on the theme could be identified; next a research was made on etymology, semantics and translation of the words that make up the realm of the anguish; and then a study on Psychopathology and its method, the clinical method. A systematic and detailed research was carried out on Fundamental Psychopathology texts related to the topic, showing that Fundamental Psychopathology makes a faint distinction between anguish and anxiety, distinguishing them on the descriptive level rather than on the terminological and theoretical ones. The research also showed, at the same time, that the relevant distinction Fundamental Psychopathology has made on the realm of anguish is between objectivity and subjectivity and not between anguish and anxiety